PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PRODUKTIVITAS MANGROVE DI DESA BADDURIH KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Kamaroellah, R. Agoes; Andriyanto, Mahalli; Firdausiyah, Nuri; Meylina, Qurrotul A'yun; Kutsiyah, Farahdilla; Syafik, Moh. (Universitas Negeri Medan, 2023)
Baddurih Village, Pademawu, Pamekasan has potential natural resources, including the Mangrove plant ecosystem. However, this ecosystem has yet to be maximized by the surrounding community, especially by the village youth. This service activity aims to provide training to motivate the community, especially village youth, to create great business opportunities by optimizing the potential of the surrounding natural resources. The method used by researchers is the ABCD method. The ABCD method was chosen because this approach is suitable for finding out what assets and potential can be utilized like this service activity, where this community empowerment activity starts from the support and strengths of the community. This service activity is more focused on the village youth, as the community closest to the beach where mangroves are cultivated has yet to be utilized optimally by the community. In this case, the training activity was the socialization of business understanding and providing innovation to process mangroves into a product with high selling value, namely Mangrove Coffee products. The output is in the form of increasing production and quality of Mangrove Coffee products, which can help the community's source of income and provide job opportunities for the community.